Inhibiting effect of p-Coumaric acid on U87MG human glioblastoma cell growth. (3rd April 2022) - Oliva, Maria Antonietta; Castaldo, Salvatore; Rotondo, Rossella; Staffieri, Sabrina; Sanchez, Massimo; Arcella, Antonietta
Abstract: p -Coumaric acid (pCA) is a hydroxycinnamic acid derivative commonly found in many natural products that has been extensively studied for its anticancer activity in multiple cell lines. In this report we investigated the effects of this phytochemical as adjuvant therapy to treat glioblastoma, an infaust brain tumour characterized by the acquired or innate resistance to the conventional chemotherapy temozolomide (TMZ). U87Mg glioblastoma cell growth and viability was assessed by growth rate curves and MTT assay incubating cells with 0.5 and 1 mM pCA for 24 h, 48 h and 72 h. Cell cycle analysis, performed by flow cytometry, showed that pCA led the accumulation of GBM cells in G2/M phase. Western blot analysis shows that pCA induced CDK4 cyclin-dependent kinase reduction and p53 increase, followed by induction of the CDK inhibitor p21. Furthermore, pCA treatment mediated the activation of apoptosis and the inhibition of migration of U87Mg cells. Finally, the treatment of glioblastoma cells in vitro with pCA concomitantly with the TMZ revealed a synergistic effect between the natural substance and the chemotherapy. In conclusion, our results demonstrated that pCA acts influencing the cell viability and cell cycle of U87Mg cells by promoting cell cycle arrest in G2/M phase and apoptosis. Abstract : UF0001